143 Is it 'CLIPPERS'? Is it CNS Hemophagocytic Lymphohistiocytosis (HLH)?. Issue 6 (27th May 2022) - Parida, Amitav; Hemingway, Cheryl; Eleftheriou, Despina; Wassmer, Evangeline
Abstract : Objective: We aim to share our experiences with an Adult Neurology audience of five children (3F, 2M) with Hemophagocytic Lymphohistiocytosis (HLH), who presented with an atypical neuroinflammatory disorder. Methods: Single institution retrospective case series: Results: Mean age of presentation was 6 years (3–11). Presenting features were headache (N=1), optic neuritis (N=1), diplopia (N=2) and hemiplegia (N=1). 4 children had MRI imaging suggestive of demyelination. One child had an isolated area of restricted diffusion in the brainstem. An initial working diagnosis of 'CLIPPERS' (Chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids) was made in three cases. Only two children ever met the criteria for systemic HLH. Pathogenic variants of RAB27A, STXBP2, UNC13 and PRF1 were separately identified in four children which are all associated with familial Hemophagocytic Lymphohis- tiocytosis (fHLH). Four children in this series have already undergone successful Haemopoietic Stem Cell Transplantation (HSCT). Conclusions: We propose that adult neurologists consider genetic panel and immunological (Natural Killer Cell function, perforin expression and granulocyte release assay) testing for HLH in cases of atypical recurrent CNS inflammation and presentations consistent with 'CLIPPERS'. Clinical management may be changed as HSCT is considered the gold standard treatment for familial HLH. Nonetheless, the long term history of these cases and risk of recurrent CNS inflammation post HSCT remains unclear. a.parida@nhs.net